Approximation of random processes by cubic splines - Kamenschykova, O. (Інститут математики НАН України, 2008)
Approximation of some classes of random processes by cubic splines with given accuracy and reliability is considered. Estimations of deviation of approximating spline from original process are obtained. A few examples of approximation are considered. Application of splines for simulation of processes is also studied.